Assortative preferences in choice of major - Yigit Aydede (IZA Journal of Labor Economics, 2020)
The primary objective of this study is to examine the contribution of available information constrained by parents' fields of study to the observed assortative preferences in their children's choice of major. Comparable to panel models, we define within-family transmission functions with 1-to-2 matches (1 for each parent). Using the confidential major file of the 2011 National Household Survey from Canada, the results show that children's choice of field of study exhibits significant assortative preferences isolated from ability sorting and unobserved differences across majors and other family characteristics. With some caution, we attribute this persisting assortative tendency to the information asymmetry across alternative majors built on by parents' educational backgrounds within families.
Keywords: J1; I2; D1; 330; field-of-study homogamy; choice of field of study; occupational relatedness